(untitled) (Research, Society and Development, 2020)
Innovation is recognized as a complex movement built from diverse dynamics. It needs to apply creativity and build new products, innovation also requires the understanding of many other socioeconomic, cultural and marketing factors involving technical-scientific training. Thus, the objective of this article is to characterize innovation in a theoretical-practical vision, triangulated with the issues of Intellectual Property and the University-Company relationship. Based on the qualitative research approach, the methodology adopted was exploratory descriptive, with the use of secondary data with the main references in the cited areas and scientific articles captured in the Scorpus platform. In addition, updated data was added in order to interweave theory and practice. In the end, there was evidence of how innovation has ratified its socioeconomic role in contemporary society. As a result, the significant role of the government-university-market relationship - Triple Hélix - as a source of innovation stimulus, appeal to creativity and specific attention to Intellectual Property was verified.